2018
DOI: 10.1080/21645515.2018.1528836
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune bovine colostrum reduces gastrointestinal carriage of uropathogenic Escherichia coli

Abstract: Debilitating recurrent urinary tract infections (UTIs) are often associated with gastrointestinal colonisation by uropathogens, such as uropathogenic Escherichia coli (UPEC), suggesting that these populations might be a suitable target for the treatment and prevention of recurrent UTI. However, antimicrobial treatment is generally unable to prevent recurrent UTI, and often selects for multidrug resistant uropathogens in the gut, and causes dysbiosis of the gut, vaginal, and urinary microbiota. Of note, the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our systematic review showed that HBC conferred a beneficial effect on acute rotavirus infection [ 33 ]. It is suggested that the vaccination of cows with uropathogenic Escherichia coli can stimulate a targeted immune response [ 57 ], which could be an interesting area for future studies. The specific type of HBC, with neutralizing titer activity against H. pylori , appears to have clinical utility in inhibiting the binding of H. pylori to lipid receptors [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review showed that HBC conferred a beneficial effect on acute rotavirus infection [ 33 ]. It is suggested that the vaccination of cows with uropathogenic Escherichia coli can stimulate a targeted immune response [ 57 ], which could be an interesting area for future studies. The specific type of HBC, with neutralizing titer activity against H. pylori , appears to have clinical utility in inhibiting the binding of H. pylori to lipid receptors [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For determination of minimum inhibitory concentrations (MIC), extracts (250 to 0.5 µg mL −1 ) or synthesized compounds (100 to 0.0002 µM) were serially diluted in microtiter plates. Bacterial suspension (90 µL, OD 600 nm 0.001) was added to each well and plates were incubated at 37 • C for either 18 h (MRSA, P. aeruginosa PAO1, E. coli EC958) or 7 days (M. tuberculosis H37Rv) as described previously (Harrison et al, 2017;Irene et al, 2019;Larcombe et al, 2019;Mouton et al, 2019). Resazurin (10 µL; 0.05% w/v) was added and plates were incubated for 3 h or 24 h (M. tuberculosis) at 37 • C. The inhibitory activity was calculated by visual determination of color change within wells or detection of fluorescence at 590 nm using a FLUOstar Omega microplate reader (BMG Labtech, Germany).…”
Section: Bacterial Inhibition Assaysmentioning
confidence: 99%
“…Immunological approaches may represent further options to eradicate intestinal carriage of MDRO, e.g. the application of hyperimmune bovine colostrum directed against globally disseminated multidrug-resistant Escherchia coli lineage ST131, which has been successfully tested in a mouse model, but is in the very early stages of development [19].…”
mentioning
confidence: 99%